A CARBON TAX IN INDONESIA : CONCEPT, OBJECTIVES AND CHALLENGES - astuti, apri dwi; Muna, Arinal (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2025)
Indonesia is among the world's ten largest emitters, as carbon emissions from fossil fuels are the primary cause of climate change. Law No. 7 of 2021 concerning Harmonization of Tax Regulations establishes a carbon tax as a policy instrument to internalize external emission costs and encourage a shift to renewable energy. It also helps meet Paris Agreement commitments. This study investigates the concept, objectives, and challenges associated with implementing a carbon tax as part of the national plan to achieve net-zero emissions (NZE) by 2060. This study uses qualitative descriptive analysis by analyzing secondary data from laws and regulations, government ministry websites, and national and international research journals. The study shows that Indonesia uses a combined cap-and-tax approach, which combines a carbon tax and a carbon market mechanism. Although the carbon tax has clear environmental and fiscal objectives, its implementation faces institutional, technical, political, and economic challenges, including policy coordination, stakeholder readiness, and potential impacts on businesses and low-income households. To ensure that emission reductions are effective without disrupting economic stability, this study found that carbon tax policies require a comprehensive, fair and aligned design with the national economic structure.